2020
DOI: 10.1002/chem.202001164
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Formation of Facial Tris‐Cyclometalated PtIV Complexes: Dual Phosphorescence from Heteroleptic Derivatives

Abstract: A stereoselective synthetic route to homo‐ and heteroleptic facial tris‐cyclometalated PtIV complexes is reported, involving the oxidative addition of 2‐(2‐pyridyl)‐ or 2‐(1‐isoquinolinyl)benzenediazonium salts to cis‐[Pt(C^N)2] precursors, with C^N=cyclometalated 2‐(p‐tolyl)pyridine (tpy), 2‐phenylquinoline (pq), 2‐(2‐thienyl)pyridine or 1‐phenylisoquinoline (piq), to produce labile diazenide intermediates that undergo photochemical or thermal elimination of N2. The method allows the preparation of derivative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…This band represents a very small fraction of the emitted photons, with a quantum yield of Φ F ≈ 0.005 in both CH 2 Cl 2 and PMMA. We have previously reported dual fluorescent/phosphorescent emissions from Pt(IV) complexes bearing flpy 65 or other C∧N ligands with extended π systems, 45 , 46 which are due to a relatively less efficient intersystem crossing to the triplet manifold as a consequence of a lower metal orbital contribution to the involved excited states and the reduced spin–orbit coupling effects induced by the metal. Excitation spectra monitored at the phosphorescent emission band correlate with the corresponding absorption profiles in all cases.…”
Section: Resultsmentioning
confidence: 99%
“…This band represents a very small fraction of the emitted photons, with a quantum yield of Φ F ≈ 0.005 in both CH 2 Cl 2 and PMMA. We have previously reported dual fluorescent/phosphorescent emissions from Pt(IV) complexes bearing flpy 65 or other C∧N ligands with extended π systems, 45 , 46 which are due to a relatively less efficient intersystem crossing to the triplet manifold as a consequence of a lower metal orbital contribution to the involved excited states and the reduced spin–orbit coupling effects induced by the metal. Excitation spectra monitored at the phosphorescent emission band correlate with the corresponding absorption profiles in all cases.…”
Section: Resultsmentioning
confidence: 99%
“…19−27 In previous contributions, we have shown that several types of Pt(IV) complexes bearing cyclometalating 2-arylpyridines may exhibit efficient and long-lived luminescence from essentially ligand-centered triplet excited states ( 3 LC) that possess a very low metal-to-ligand charge-transfer (MLCT) admixture. 19,20,22,23,27 These characteristics make them promising candidates for applications that take advantage of relatively long excited-state lifetimes, such as sensing, singletoxygen sensitization, or photocatalysis. Although small, the extent of the MLCT contribution to the emissive state has been observed to fluctuate depending on the coordination environment, causing variations in the radiative rates.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The associated HOMO energies vary according to the sequence 3c < 3a < 3d < 3e and agree with previously determined C ∧ Nbased π-orbital energies in cyclometalated Pt(IV) complexes. 19,20,27 The isomeric pairs 3a/5a and 3d/5d possess identical HOMO energies, suggesting that the HOMO is also primarily a π-orbital of the C ∧ N ligand in complexes 5a and 5d. The first reduction is irreversible for all complexes and is visible in the range from −1.54 to −1.69 V vs SCE for 3a−e, whereas for 5a and 5d it appears at distinctively less negative potentials (−1.41 or −1.43 V vs SCE, respectively).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The synthesis of tris-cyclometalated Pt(IV) complexes with a fac conguration is challenging [46][47][48] and only in one previous instance has a crystal structure been successfully solved. 49 The above described results indicate that the insertions of alkynes into the Pt-H bond of 3aa require the presence of at least one electron-withdrawing group, implying an electrophilic behaviour of the alkyne. Since most of the tested internal alkynes were found unreactive, it is also clear that the steric requirements of the alkyne substituents have a detrimental effect.…”
Section: Alkyne Insertion Reactionsmentioning
confidence: 80%